THE EFFECTIVENESS OF INQUIRY-BASED LEARNING IN PROXIMITY SENSOR PRACTICUM TO IMPROVE STUDENT UNDERSTANDING - Syafar Farouk, Irfan; Sulistiani, Fitria Ayu; Chusni, Muhammad Minan; Kariadinata, Rahayu; Sanjaya, Mada (Fakultas Sains dan Teknologi UIN Sunan Gunung Djati Bandung, 2025)
Laboratory practicum is essential for understanding abstract concepts, and the Inquiry Based Learning model is often applied in this context. This study aims to measure the level of effectiveness of implementing inquiry based learning in an electronics practicum on analog proximity sensor material towards improving student concept understanding. This study uses a quantitative approach with a One-group pretest-posttest design involving 27 3rd-semester students from the Physics Department of UIN Sunan Gunung Djati Bandung. Data were analyzed using the Shapiro-Wilk normality test, hypothesis testing (paired t-test), and N-Gain analysis. The results showed that the pre-test (Sig. 0.054) and post-test (Sig. 0.089) data were normally distributed. The t-test showed a very significant difference (Sig. 0.000) between the pre-test (46.29) and post-test (73.70) mean scores. Despite a significant increase, the N-Gain Percent analysis showed an average effectiveness of 51.93%, which falls into the